Mechanical analysis for a keyless anti-theft bicycle lock system prototype - Ismail I.N.; Zuhair Zakariya M.A.; Azman N.S.; Zawawi M.H.; Zahari N.M.; Abidin S.Z.; Mahmood Zuhdi A.W.; Eqwan M.R.; Mohamed H.; Ramli M.Z.; Mansor M.H.; Syaifoelida F.; et al. (American Institute of Physics Inc., 2023)
The purpose of this paper is to identify the suitable design to develop a prototype of keyless anti-theft bicycle lock system. Student bicycle commuters are not satisfied with the present selection of bicycle locks accessible. Many express that locking their bicycle isn't a simple procedure. User contemplates showed that u-locks are seen to be the strongest and rent powerless to breaking; anyway they are inconvenient and badly designed to utilize. Cable locks are light weight; however, they are can get effortlessly cut. Different methods are costly and require significant modifications to the bicycle. These regular locks are not by any means effective in theft anticipation and this is an outstanding issue. The attempts to tackle this issue included either designing brand new locking system or enhancing the current locks by adding features. 2021 American Institute of Physics Inc.. All rights reserved.